A Case of Gardner's Syndrome Presenting as an Abdominal Wall Mass - Kim, Ji Eun; Kim, Ja Seon; Suh, Byung Sun; Kwon, Kye Won; Park, Ju Sang (Intestinal research, 2013)
Familial adenomatous polyposis (FAP) is characterized by large numbers of adenomatous polyps in the colon and inherited as an autosomal dominant disease. Gardner’s syndrome is a form of FAP accompanied by extra-colonic tumors and desmoid tumors. Desmoid tumors are rare, and benign tumors characterized by fibroblastic proliferation of fascial and musculoaponeurotic components. There is an approximate 1,000 times higher incidence of desmoid tumors in patients with FAP compared with the general population. Desmoid tumors in Gardner’s syndrome occur in the small bowel mesentery in 80% of all cases, and the other 20% in the abdominal wall or the extremities. Almost all cases of desmoid tumors in Gardner’s syndrome were incidentally found after prophylactic total proctocolectomy for colon cancer prevention in the patients with FAP. We report a case of Gardner’s syndrome associated with codon 1099 mutation of the adenomatous polyposis coli gene, in which the patient was initially found to have desmoid tumors and subsequently diagnosed as FAP by screening colonoscopy. (Intest Res 2013;11:217-222) KCI Citation Count: 0